Pembelajaran Matematika Menyenangkan bagi Anak Usia Dini melalui Media Fuzzle Interaktif - Eva Monika Safitri Lubis; Didik Reski Suryani; Fitriani Fitriani; Adek Safitri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
In the midst of the Covid-19 pandemic, teachers and children (students) have had to undergo an educational transformation that suddenly forced them to embrace digital learning to support online teaching. In the context of mathematics, teachers can use interactive media as a digital device that can trigger active, fun math understanding for early childhood. The purpose of this study was to see student acceptance during learning using interactive puzzle media. This research method is a qualitative method and literature study. The results showed that interactive puzzle media can improve the ability to recognize geometric shapes in early childhood. Because interactive puzzle media is a learning medium that can improve aspects of early childhood development, when using interactive puzzle media children do not feel they are learning but they are playing and by using interactive puzzle media children's learning activities become more fun so children are more interested in learning. follow the learning and the learning outcomes obtained will be better.Â